Thermal servo-controlled systems in the management of VLBW infants at birth: A systematic review - Ercolino, Orietta; Baccin, Erica; Alfier, Fiorenza; Villani, Paolo Ernesto; Trevisanuto, Daniele; Cavallin, Francesco (Frontiers in Pediatrics, 2022)
Background Thermal management of the newborn at birth remains an actual challenge. This systematic review aimed to summarize current evidence on the use of thermal servo-controlled systems during stabilization of preterm and VLBW infants immediately at birth. Methods A comprehensive search was conducted including MEDLINE/Pubmed, EMBASE, SCOPUS, clinicaltrials.gov, and the Cochrane Database through December 2021. PRISMA guidelines were followed. Risk of bias was appraised using Cochrane RoB2 and Risk Of Bias In Non-Randomized Studies of Interventions (ROBIN-I) tools, and certainty of evidence using GRADE framework. Results One randomized controlled trial and one observational study were included. Some aspects precluded the feasibility of a meaningful meta-analysis; hence, a qualitative review was conducted. Risk of bias was low in the trial and serious in the observational study. In the trial, the servo-controlled system did not affect normothermia (36.5-37.5°C) but was associated with increased mild hypothermia (from 22.2% to 32.9%). In the observational study, normothermia (36-38°C) increased after the introduction of the servo-controlled system and the extension to larger VLBW infants. Conclusion Overall, this review found very limited information on the use of thermal servo-controlled systems during stabilization of preterm and VLBW infants immediately at birth. Further research is needed to investigate the opportunity of including such approach in the neonatal thermal management in delivery room.